The Effect of Educational Units According to the Cognitive Training Strategy in Learning the Football Handling Skill - Nashmi, Muneeb Hassan; Rashid, Abdul Rahman Nasser; Dhiab, Adel Abbas (Indonesian Journal Publisher, 2024)
The importance of the cognitive training strategy for students’ learning in the first stage in football handling was addressed. The research problem was to answer the question: Do the educational units applied by the researchers have a positive role in learning the football handling skill? The aim of the research was to prepare educational units using the cognitive training strategy in Learn the skill of handling football. Where the research areas were: The human field: First stage students in the College of Basic Education, Department of Physical Education and Sports Sciences / Al-Mustansiriya University, Time field: for the period from 10-12-2022 until 10-2-2023. The research population was represented by the students of the first stage in the College of Basic Education - Al-Mustansiriya University (70) students, and the research sample consisted of two equal groups (10) control and experimental. The researchers conducted pre-tests for the research sample, then applied the main experiment for a period of 10 weeks, after which the researchers conducted the post-tests by applying The same procedures were used in the pre-tests, which indicated that there were significant differences between the two groups, in favor of the experimental group. The conclusions showed that there was a positive impact of the educational units used in the research to learn the skill of handling, and the researchers recommended using the cognitive training strategy to learn other skills.